Association of primary central nervous system vasculitis with the presence of specific human leucocyte antigen gene variant - Krämer, Markus; Berlit, Peter (Clinical neurology and neurosurgery, 2017)
Objectives: The etiology and genetic susceptibility of primary central nervous system vasculitis (PCNSV) are still unclear.Patients and methods: We analyzed the DNA of 25 Caucasian patients with PCNSV for human leucocyte antigen genes HLA-A, HLA-B, HLA-DRB1, and HLA-DQB1, respectively. HLA-frequencies of the 25 patients with PCNSV were compared with HLA-frequencies of matched Caucasian controls. Results: No statistically significant associations were found for HLA-B, HLA-DR1 and HLA-DQB1 variant. In the PCNSV group, only the HLA-A*69 variant was found more often than expected statistically. Conclusion: The results of this study indicate a potential association of HLA marker with PCNSV in Caucasian patients. Further studies are needed to elucidate the role of genes within the human major histocompatibility complex in the pathogenesis of this angiopathy.